Polymers as nanocarriers for controlled drug delivery - Calderón, Marcelo (Henry Stewart Talks, 2018)
Definition and introduction of polymers as nanocarriers, Mechanisms and triggers for controlled drug delivery, Biological fate of polymeric nanocarriers, The use of polymer-drug conjugates for anticancer therapy, Examples of thermoresponsive nanogels and polymeric nanoparticles for hair follicle penetration for topical drug delivery